IMAM’S DEVIATION IN NAWAL EL SAADAWI’S THE FALL OF THE IMAM NOVEL (1989): A PSYCHOANALYTIC APPROACH - HIDAYAH, NURUL (2011)
The major problem of this study is to reveal the Imam’s deviation in Nawal El Saadawi’s The Fall of the Imam novel. The objectives of the study are: to analyze structural elements of the novel and to analyze Nawal El Saadawi’s The Fall of the Imam novel based on psychoanalytic approach, especially Freud’s theory. In analyzing the data, the researcher applies two approaches; they are structural analysis approach and psychoanalytic analysis approach. Structural analysis approach is used to analyze the elements of the novel. It consists of character and characterization, setting, plot, point of view, style and theme. While, the psychoanalytic analysis approach is used to analyze the Imam’s deviation which has influences to his personality. Based on the analysis, the researcher draws the following conclusions: firstly, the researcher concludes that Saadawi integrates the structural elements of the novel in such a way that they build a good unity. Secondly, the deviation rises because of drives from system of personality, which consists of id, ego and superego. It is begun by the internal conflict of the major character of the Imam. The Imam is Bint Allah’s father, an illegitimate daughter. He is described as an authoritative religious ruler in Islamic society believed to be representative of God who uses his authority in bad way. The id happens when he wants to control the throne on earth and a throne in heaven. He wants to get everything without paying attention to the surroundings. When the id wants to satisfy soon, superego must consider with moral. It will raise conflict in the personality. Then if the conflict can not be solved, it raises the deviation and the person will not be composed.